THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE JOB SATISFACTION WITH INCENTIVES AS AN INTERVENING VARIABLE (Case Study on Medical doctor and Nurses in Wisconsin City Area) - Mohsen Bahmani-OSKooee; Bob Feinberg (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
In this study, the population was employees of Medical doctor and Nurses in Wisconsin City Area, namely 31 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population is 31 employees of Medical doctor and Nurses in Wisconsin City Area. it can be concluded that the first hypothesis is accepted, meaning that work discipline (X) has a significant effect on job satisfaction (Y). the second hypothesis is accepted, meaning that incentives (Z) have a significant effect on job satisfaction (Y). the third hypothesis is rejected, meaning that incentives (Z) are not an intervening variable that mediates the effect of work discipline (X) on job satisfaction (Y).